2021
DOI: 10.3390/su13020837
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Untreated and Acidified Biochar on NH3-N Emissions from Slurry Digestate

Abstract: The development of new options to reduce ammonia (NH3) emissions during slurry manure storage is still required due to the shortcomings of the current technologies. This study aimed to identify to what extent untreated and acid-treated biochar (BC) and pure acids could reduce ammonia nitrogen (NH3-N) volatilization and increase nitrogen retention in slurry digestate. The NH3-N emissions were effectively reduced by H2SO4 and H3PO4 acids, untreated BC when applied mixed into the digestate and acidified BC treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Because the nitrogen input did not correlate with N uptake by plants ( Figure 4B ), a possible explanation for this could be the lowered losses of nitrogen: lower pH putatively mediated reduction of ammonium to non-volatile cation form, and its volatilization was further mitigated due to enhanced nitrogen transformation and mineralization activities. A study done with slurry digestate showed that NH 3 emissions were lower when it was acidified ( Covali et al., 2021 ). Decreased TN content in the M+BB variant could have been coupled with decreased nitrogen mineralization, determined by urease (Ure) activity (compared to other legume-based digestate variants); see Figure 6A .…”
Section: Discussionmentioning
confidence: 99%
“…Because the nitrogen input did not correlate with N uptake by plants ( Figure 4B ), a possible explanation for this could be the lowered losses of nitrogen: lower pH putatively mediated reduction of ammonium to non-volatile cation form, and its volatilization was further mitigated due to enhanced nitrogen transformation and mineralization activities. A study done with slurry digestate showed that NH 3 emissions were lower when it was acidified ( Covali et al., 2021 ). Decreased TN content in the M+BB variant could have been coupled with decreased nitrogen mineralization, determined by urease (Ure) activity (compared to other legume-based digestate variants); see Figure 6A .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been concerning the use of biochar as a bio-cover or bio-mix for reducing NH3 emissions with showing variable effectiveness in reducing emissions showing that the efficiency was highest in the first week and gradually reduced over the period (Miirkhanuly et al, 2020;Covali et al, 2021). However, McGuiggan et al (2022) did not show any reduction in NH3 emissions with applying biochar.…”
Section: Introductionmentioning
confidence: 99%